Impact of Multidisciplinary Cleft Team Care on Oral Health Quality of Life in Children With Unilateral Cleft Lip and Palate: A Focus on Early Intervention vs. Sporadic Treatment - Shabnam Ajami; Mahtab Ebrahimi Nezhad; Faezeh Bahraini; Nasser Nadjmi; Maryam Zeraatkar (International Journal of Dentistry)
Conclusions: The team-managed group obtained better scores in all subscales in comparison to the control and the non-team patient groups; however, since randomization and a controlled surgical method were not possible, the improvements in quality-of-life scores cannot be directly related to the surgical method.